Understanding the venous–arterial CO2 to arterial–venous O2 content difference ratio (2016)
Introduction Early identification of tissue hypoperfusion is a cornerstone of shock management [1]. Normal macrohemodynamic and oxygen-derived parameters do not, however, rule out the presence of tissue hypoxia [2]. In this setting, carbon dioxide (CO2)-derived variables may provide information on macroand microvascular blood flow [3] and also on the presence of anaerobic metabolism [4, 5]. Importantly, variations in CO2 occur more rapidly than changes in lactate kinetics, making the former an attractive biomarker for monitoring, especially during the early stages of resuscitation [6, 7].